An Experimental and FEM Modal Analysis of Cracked and Normal Steam Turbine Blade. (2015) - Shukla, Akash; Harsha, S.P.
Abstract: This work concerns with comparative study of the model analysis of steam turbine blade with the analytical method and Experimental Method. In any steam turbine the last stage blades are most prone for the failure due to severe dynamic conditions of loading. NFT of these blades in lab conditions is mandatory to detune these blades. First the modal analysis of last stage blade is carried out with the help of FEM techniques then the blade is tested in NFT lab and the natural frequency calculated by both the methods is compared. After the validation of model through experimental results the similar study is also carried out for a cracked blade. Finally the variation in natural frequency and mode shapes for cracked and un-cracked blade is studied.